Potential Wound Healers from Plant Origin - V. Habbu, Prasanna; Joshi, Hanumanthachar; Patil, B. S. (Pharmacognosy Reviews)
Herbal medicine (medicinal plants, polyherbal formulations) is still the mainstay of about 75-80% of world population, mainly in the developing countries for primary health care. Wound is a loss of cellular and anatomic or functional continuity of living tissues. Wound healing proceeds in three interrelated dynamic phases, irrespective of the wound type and degree of tissue damage. This sequence of physiological events occurs by a process of connective tissue repair. In view of this a detailed review of literature was carried out on natural prohealers, phytoconstituents, polyherbal formulations and various nutraceuticals responsible for wound healing activity, with special emphasis on different stages of wound healing, which could be of enormous help in managing and treating various types of wounds.
Keywords: formulations; nutrients; phytochemicals; pro-healers; wound healing